THE ROLE OF PARENTS AS FACILITATORS IN HELPING CHILDREN TO LEARN DURING THE COVID-19 PANDEMIC - Swastika, Luh Santi; Choiriyah, Choiriyah (Journal of Early Childhood Education (JECE), 2022)
This study explores parents' role as facilitators in assisting children in online learning during the Covid-19 pandemic. The methodology in this study uses qualitative data collection methods using observations and interviews. The informants who participated were 20 parents, and the data analysis used triangulation of data sources with the approach of Miles and Huberman. The findings of the results show that the role of parents as facilitators can facilitate students with various kinds of electronic devices and a variety of children's learning environments. Several obstacles are faced by parents, namely being patient in dealing with the attitudes and behavior of children, guiding their children to always behave well to anyone, accompanying children to learn online, and teaching children to learn independently in completing their school assignments.